Women Rule: Preferences and Fertility in Australian - Fan, E; Maitra, P (My University, 2012)
Using a unique data set from Australia, we investigate how individual fertility pref- erences translate into fertility realizations. We find consistent evidence that the wife's preference is more important than the husband's preference in predicting subsequent births, no matter whether her initial fertility desire is higher or lower than that of her partner. We also explore the effects of the introduction of the non-means-tested Baby Bonus introduced in 2004 by testing whether the hypothesis that the cash transfers from the scheme increase the bargaining power of the partner with higher fertility rate, thus leading to an increase in fertility for couples with disagreement on fertility plan. Our findings do not support this hypothesis, neither do they suggest any significant fertility-enhancing effect of the scheme.
Keywords: Benefits and Payments; Families -- Fertility; Families and relationships; Families; Benefits and Payments; Fertility; Families and relationships